Mechanical load modulates the cargo of secreted extracellular vesicles (EVs) from living myocardial slices. (25th November 2020) - Nicastro, L; Catapano, F; Nunez Toldra, R; Floriano, J; Oliveira, C.C; Emanueli, C; Terracciano, C.M.N
Abstract: Introduction: Mechanical overload plays an important role in the progression of chronic heart failure (CHF). Beside the numerous neurohormonal and chemical stimuli that contribute to structural and functional changes in the myocardium, intercellular communication mediated by extracellular vesicles (EVs), also plays a pivotal role in disease progression. Exosomes are a subset of EVs ranging between 30–150 nm; these mediators carry molecular cargoes such as miRNAs, mRNAs, DNA and several proteins. However, it is still unclear how specific pathological stimuli may induce a change in their release from tissues or a difference in their cargo content. Living myocardial slices (LMS) are ultra-thin sections of heart tissue, ranging from 100–400 μm in thickness. They retain the multicellularity, electromechanical physiology, biochemistry and extracellular matrix of the adult heart. Purpose: To investigate whether mechanical load influences both the released amount and content of LMS-derived exosomes after 24 hours culture. Methods and results: LMS were prepared from the left ventricle of male Sprague Dawley rats using a high precision vibratome. LMS were stretched in the direction of the muscle fibers at a sarcomere length (SL) of 2.2 μm to recapitulate physiological preload, and at 2.4 μm SL to recapitulate a condition of volume overload. LMS were cultured for 24 hours under electromechanical stimulation. Media containing LMS-derived exosomes was harvested after culture and processed for exosome isolation by size exclusion chromatography columns. Particle size and concentration were assessed by nanoparticle tracking analysis and protein quantity by microBCA assay. There was no significant difference in the size of exosomes between overload and physiological conditions, with an average mean size of 113.475±8.35 nm for the physiological and 129.3±16.35 nm for the overload condition (p=0.61; n=4 physiological; n=3 overload). Although there was not significant difference in exosome amount between physiological and overload condition, (7.00E+10±2.53E+09 vs 1.04E+11±5.77E+09 particles/ml) (p=0.57; n=4 physiological; n=3 overload), exosomes released from overloaded LMS showed a significant increase in protein content compared to physiologically loaded LMS (150.57±25.682 vs 66.045±9.855 μg/ml) (p=0.04; n=3 overload; n=2 physiological). Conclusions: Mechanical load influences the cargo content of EVs secreted from LMS after 24 hours culture under electromechanical stimulation. Understanding how mechanical load correlates with specific cargoes in EVs will reveal novel therapeutic targets for the treatment of CHF. Funding Acknowledgement: Type of funding source: Private grant(s) and/or Sponsorship. Main funding source(s): British Heart Foundation (BHF)